2019
DOI: 10.25139/jkp.v3i2.2006
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh destination image dan subjective norm terhadap biat berkunjung wisata sunan ampel surabaya

Abstract: One of the attractions in East Java that is visited by many tourists is the religious tourism area of the Sunan Ampel Mosque. The enchantment of culture, art and history contained in the Sunan Ampel Mosque has a special attraction for tourists. The 2014 data states that the tomb of Sunan Ampel in Surabaya became the most visited location of pilgrims, namely more than 1.9 million visits. Therefore, this study aims to determine the effect of destination and subjective norms on the intention to visit Sunan Ampel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
2
0
2
Order By: Relevance
“…Previous research results have confirmed the positive influence of religiosity and destination image on intentions to visit halal tourist destinations (Chi & Qu, 2008;Y. Liu et al, 2018;Purnasari et al, 2018;Ramadhani & Kurniawati, 2019). Therefore, the following hypothesis is put forward: H9: Religiosity is able to moderate the influence of destination image on intentions to visit halal tourism on Lombok Island.…”
Section: The Influence Of Destination Image On Intentions To Visit Ha...mentioning
confidence: 74%
“…Previous research results have confirmed the positive influence of religiosity and destination image on intentions to visit halal tourist destinations (Chi & Qu, 2008;Y. Liu et al, 2018;Purnasari et al, 2018;Ramadhani & Kurniawati, 2019). Therefore, the following hypothesis is put forward: H9: Religiosity is able to moderate the influence of destination image on intentions to visit halal tourism on Lombok Island.…”
Section: The Influence Of Destination Image On Intentions To Visit Ha...mentioning
confidence: 74%
“…This is where pilgrimage functions to make tourists feel committed to being responsible for themselves and others. In the end, tourists on these trips try to stay true to their rituals (Ramadhani & Kurniawati, 2019).…”
Section: Figure 1 Muslim and Non-muslim Tourists Visit The Tomb Of Su...mentioning
confidence: 99%
“…Sedangkan menurut Kim dan Kwon (2018) ketika seorang wisatawan memiliki perilaku perjalanan maka niat berkunjung mewakili rencana wisatawan untuk melakukan perilaku perjalanan di masa depan, niat untuk berkunjung ini telah dipelajari secara ekstensif dalam penelitian pariwisata sebagai sinyal loyalitas pelanggan. Visit Intention merupakan katalis yang didapat oleh para wisatawan untuk memutuskan berkunjung ke suatu lokasi wisata (Ramadhani & Kurniawati, 2019).…”
Section: Tinjauan Literatur Visit Intentionunclassified